(untitled) (mathematica didactica, 2025)
Digital media and the availability of data on an almost unlimited scale are radically changing our access to information. Given the abundance of data, people (students, citizens, ...) need to be aware of their limitations and potential biases as well as the limitations and potential errors of the statistical models and methods used. In order to increase resilience to misinformation, manipulation and fake news, we need to design our teaching in such a way that it supports the critical and informed use of data and models. The following article presents an innovative interdisciplinary concept and its implementation in teacher training programs